Determination of Gibbs energies of formation in aqueous solution using chemical engineering tools. (August 2016) - Toure, Oumar; Dussap, Claude-Gilles
Highlights: The standard Gibbs energy of formation is important in metabolism studies. This study enables to reduce the confusion encountered when looking for missing data. The differences between pure compound and infinite dilution properties were clarified. We provide the thermodynamic relations used to convert these properties consistently. Quantum based tools and thermodynamic tables enable to complete existing databanks. Abstract: Standard Gibbs energies of formation are of primary importance in the field of biothermodynamics. In the absence of any directly measured values, thermodynamic calculations are required to determine the missing data. For several biochemical species, this study shows that the knowledge of the standard Gibbs energy of formation of the pure compounds (in the gaseous, solid or liquid states) enables to determine the corresponding standard Gibbs energies of formation in aqueous solutions. To do so, using chemical engineering tools (thermodynamic tables and a model enabling to predict activity coefficients, solvation Gibbs energies and pKa data), it becomes possible to determine the partial chemical potential of neutral and charged components in real metabolic conditions, even in concentrated mixtures.